Unconventional government debt purchases as a supplement to conventional monetary policy - Martin Ellison; Andreas Tischbirek (Bank of Finland, 2013)
In response to the Great Financial Crisis, the Federal Reserve and the Bank of England have adopted unconventional monetary policy instruments. We investigate if one of these, purchases of long-term government debt, could be a valuable addition to conventional short- term interest rate policy even if the main policy rate is not constrained by the zero lower bound. To do so we add a stylised financial sector and central bank asset purchases to an otherwise standard New Keynesian DSGE model. Asset quantities matter for interest rates through a preferred habitat channel. If conventional and unconventional monetary policy instruments are coordinated appropriately then the central bank is better able to stabilise both output and inflation.
URN:NBN:fi:bof-20140807647
Keywords: E40; E43; E52; E58; 330; Quantitative Easing; Large-Scale Asset Purchases; Preferred Habitat; Optimal Monetary Policy